Insights into the Tectonic Framework of the Benin Basin from Satellite Gravity Data Interpretation - Lawson-Jack, Osaki (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2025)
Satellite gravity data were interpreted to characterise the basement morphotectonic features and architecture beneath the Benin Basin of Nigeria. The Bouguer anomaly data was processed using the high-pass filter to generate the residual anomaly grid, which formed the basis for other edge enhancement techniques like the first vertical derivative (1VD), and tilt angle derivative (TDR) in order to map linear geological features of interest. The interpreted lineaments showed major trends in the NNE-SSW, ENE-WSW, NNW-SSE, N-S, and E-W directions. 2D forward modeling of the basement architecture revealed structural mini basins located offshore of the study region. The mini basins may have accommodated over 4 km thick sedimentary packages, indicating that they have great potentials for hydrocarbon prospectivity if the right conditions for the existence of all the petroleum systems elements are met. It is recommended that future exploration efforts be concentrated on the identified mini basins to ascertain their potential through well test drilling and prospect generation in the Benin Basin of Nigeria.